Analysis of Work Readiness of Apron Movement Control (AMC) Officers in Handling Return to Apron at Adi Soemarmo Airport Surakarta - Vinsensia Amita Inviola Meo Due; Kifni Yudianto (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study discusses the work readiness of Apron Movement Control (AMC) officers in handling return to apron at Adi Soemarmo Airport Surakarta. This is because in the case of return to apron often occurs suddenly or unexpectedly and in a short time, AMC officers must make decisions quickly and precisely. For this reason, the purpose of this study is to determine the work readiness of Apron Movement Control (AMC) officers in handling return to apron, obstacles faced in handling return to apron at Adi Soemarmo Airport Surakarta. This research was conducted from October 1, 2022 to November 30, 2022. The type of research used is a qualitative research method. The data sources used are primary data and secondary data. Primary data are obtained through interviews, observations. Secondary data are obtained from reports, literature studies and images / photos that support research. The results showed that Apron Movement Control (AMC) officers were ready to handle the return to apron at Adi Soemarmo Airport Surakarta. This is observed from four aspects of job readiness, namely skills, knowledge, understanding, and personal attributes. To prepare AMC officers who are ready for their duties, it is necessary to carry out formal education and informal education. Formal education is obtained through the last education of AMC officers, socialization and other work experience. Informal education is obtained through debriefing provided by AMC colleagues and seniors as well as work experience in the field carried out every day. However, from the results of this study, obstacles are still found to be the late initial report by technicians from airlines that experience return to apron (RTA) and the lack of AMC personnel can have an impact on the performance and productivity of officers will decrease